2019
DOI: 10.1371/journal.pone.0220073
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of walking speed and slope on pedobarographic findings in young healthy adults

Abstract: Background This study aimed to investigate the effects of walking speed and slope on foot pressure changes in young healthy adults. Methods Twenty young healthy adults (mean age 22.4 years, SD 1.2 years; 10 male and 10 female) participated in the study. Dynamic pedobarographic data during treadmill walking were obtained for combinations of three different walking speeds (3.2 km/hr, 4.3 km/hr, and 5.4 km/hr) and 5 different slopes (downhill 8 degrees, downhill 4 degrees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The MPP and PTI are commonly used measures to assess the foot biomechanics with different movements and related to foot pain and the development of foot ulcers in diabetic patients [ 32 ]. The plantar of the foot in this study is divided into five specific areas: toes, metatarsal heads, medial midfoot, lateral midfoot, and heel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPP and PTI are commonly used measures to assess the foot biomechanics with different movements and related to foot pain and the development of foot ulcers in diabetic patients [ 32 ]. The plantar of the foot in this study is divided into five specific areas: toes, metatarsal heads, medial midfoot, lateral midfoot, and heel.…”
Section: Resultsmentioning
confidence: 99%
“…Footwear research has investigated the biomechanical changes of the lower limbs at different walking speeds [ 30 , 31 , 32 ] and found that an increased speed of gait results in greater ground reaction forces (GRFs). The shape of the foot tends to easily deform when walking at different speeds with changes in loading.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have shown that vGRFs increased as speed increased during level walking [62,63]. Koo et al [22], in a recent study, found that peak pressures in both the forefoot and rearfoot decrease when walking on uphill and downhill slopes of 4 and 8 degrees at lower speeds compared to higher speeds. Other researchers [64], who examined ground reaction force profiles during inclined running at iso-efficiency speeds-speeds maintaining the same metabolic intensity as level running-found that running at 4% and 8% inclinations, with lower speeds compared to level running, resulted in significantly reduced peak vertical ground reaction forces as the treadmill incline increased.…”
Section: Vertical Ground Reaction Forcesmentioning
confidence: 97%
“…On similar terrain gradients, other studies employing force platforms embedded in the surface of a ramp [14,19,20] or adapted on treadmills [15] have concentrated on investigating the impacts of uphill and downhill walking at preferred speeds on vGRFs [14,15,19,20]. Additionally, some researchers, utilizing insoles [21] and sensor matrices [22], have investigated the distribution of plantar pressures under similar experimental conditions. However, despite the valuable information offered by the studies implementing self-selected speeds that replicate everyday walking conditions, promoting more natural movement patterns and reducing stress, their applicability to the general population may be limited due to potential individual variations and responses to walking conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The unevenness may be the result of unavoidable human error in man-made work or an environmental effect, such as ramps used to reach buildings or pavement on slopes, respectively [15]. There has been an increase in research on the effects of incline surfaces while standing [16, 17−20] moving around while running [12,18], walking [19,20], or doing both [20,21], in recent years. For example, kinematics [22,23], kinetics, muscle response [24], protheses, and pathological cases [25] have all been studied in relation to incline walking.…”
Section: Literature Reviewmentioning
confidence: 99%